Karyotypes and Morphological Variability of Crayfish Pontastacus leptodactylus and P. angulosus (Malacostraca, Decapoda) - Kostyuk, V.S.; Garbar, A.V.; Mezhzherin, S.V. (Вестник зоологии, 2013)
The existence on the territory of Ukraine of two sympatric widespread species definitely different by their chromosome number was proved based on the meiotic chromosome preparations. Besides the nominal species Pontastacus leptodactylus (Dana, 1852) with modal haploid chromosome number n = 93 we prove the existence of P.?angulosus (Rathke, 1837) with n = 88.